Inhibitory effects of cynaropicrin on human melanoma progression by targeting MAPK, NF‐κB, and Nrf‐2 signaling pathways in vitro. (15th October 2020) - De Cicco, Paola; Busà, Rosalia; Ercolano, Giuseppe; Formisano, Carmen; Allegra, Mario; Taglialatela‐Scafati, Orazio; Ianaro, Angela
Abstract : Malignant melanoma is the deadliest skin cancer, due to its propensity to metastasize. MAPKs and NF‐κB pathways are constitutively activated in melanoma and promote cell proliferation, cell invasion, metastasis formation, and resistance to therapeutic regimens. Thus, they represent potential targets for melanoma prevention and treatment. Phytochemicals are gaining considerable attention for the management of melanoma because of their several cellular and molecular targets. A screening of a small library of sesquiterpenes lactones selected cynaropicrin, isolated from the aerial parts of Centaurea drabifolia subsp. detonsa, for its potential anticancer effect against melanoma cells. Treatment of human melanoma cells A375 with cynaropicrin resulted in inhibition of cell proliferation and induction of caspase‐3‐dependent apoptosis. Furthermore, cynaropicrin reduced several cellular malignant features such migration, invasion, and colonies formation through the inhibition of ERK1/2 and NF‐κB activity. Cynaropicrin was able to reduce intracellular reactive oxygen species generation, which are involved in all the stages of carcinogenesis. Indeed, cynaropicrin increased the expression of several antioxidant genes, such as glutamate–cysteine ligase and heme oxygenase‐1, by promoting the activation of the transcription factor Nrf‐2. In conclusion, our results individuate cynaropicrin as a potential adjuvant chemotherapeutic agent for melanoma by targeting several protumorigenic signaling pathways.